1994
DOI: 10.1111/j.1432-1033.1994.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

The interactions of Escherichia coli trp repressor with tryptophan and with an operator oligonucleotide

Abstract: The effects of the binding of the corepressor l‐tryptophan and an operator oligonucleotide to Escherichia coli trp repressor have been studied, using selective 15N labelling to permit observation of the backbone amide resonances of 50 of the 107 residues of the protein monomer. Repressor molecules selectively labelled in turn with [15N]alanine, [15N]glutamate, [15N]isoleucine, [15N]leucine and [15N]methionine were prepared by isolating them from prototrophic E. coli cells grown in media containing a mixture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
(48 reference statements)
2
20
0
Order By: Relevance
“…The switch from high to low salt buffer resulted in substitution of a fast chemical exchange between free and complexed protein, for one of intermediate exchange, typically occurring on the millisecond timescale (34,35). Intermediate exchange line-broadening for resonance signals emanating from the recognition helices of helix-turn-helix motifs is a recurrent theme in protein-DNA complexes (36)(37)(38), and has also been noted to occur with Ada-N (39). Such localised linebroadening has been attributed to flexibility within the protein-DNA interface (40).…”
Section: Resultsmentioning
confidence: 99%
“…The switch from high to low salt buffer resulted in substitution of a fast chemical exchange between free and complexed protein, for one of intermediate exchange, typically occurring on the millisecond timescale (34,35). Intermediate exchange line-broadening for resonance signals emanating from the recognition helices of helix-turn-helix motifs is a recurrent theme in protein-DNA complexes (36)(37)(38), and has also been noted to occur with Ada-N (39). Such localised linebroadening has been attributed to flexibility within the protein-DNA interface (40).…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 C]Glutamate labeling is expected to be more difficult, when compared with aspartic acid labeling (39,53). However, we found reasonable (41%) amounts of labeling from […”
Section: Resultsmentioning
confidence: 99%
“…This took about 3 h. At this time, 0.2 ml of 0.2 M isopropyl-1-thio-␤-D-galactopyranoside was added to induce MSP production. In addition, a 100-ml solution of 10% lactose was added; lactose was found to improve the labeling efficiency (39). After induction, the cells were grown for an additional 4 h and harvested.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative possibility is that there are exchange processes which specifically involve the non-hydrogen bonded imino protons of unpaired G and U bases located in the flexible regions of the RNA motif (such as the bulge in the middle) and further detailed studies are required to identify the specific motions responsible for the observed line broadening. This phenomenon is paralleled by the selective line-broadening observed for the backbone peptide NH protons in the spectra of selectively labelled 15 N-trp repressor on binding to the operator oligonucleotide [29]. Here the broadening selectively affects residues, most notably, in the flexible DNA-binding helix-turn-helix domain.…”
Section: Nmr Assignment Of Imino Protons and Titration With Amicetinmentioning
confidence: 77%